Algorithms and implementations to overcome practical issues in active noise control systems - Shi, Dongyuan (Nanyang Technological University, 2020)
Noise control has garnered increasing attention, in the face of growing urbanization. To deal with the noise issue, the active noise control (ANC) technique is revisited in the thesis. The ANC technique utilizes a sensor to acquire the noise information and synthesizes the anti-noise by driving the actuator to cancel the noise. Compared to the traditional passive noise control approach, it shows the apparent advantages of the cost, size, and easy deployment. Hence, ANC is widely used in active control headphone and in automotive interiors. However, the ANC technique still possesses many practical challenges, such as the nonlinearity of the secondary path, the placement of the error sensor, and the soaring computational requirements with the increasing scale of multichannel active noise control (MCANC) systems. To effectively solve these practical issues, the thesis firstly reviews existing optimization techniques and subsequently proposes unique algorithms and methods.